Construction of laser raman system using diode laser and Its performance - Abedin, Kazi M; Habib, M Ahasan; Wahadoszamen, M; Talukder, Aminul I; Haider, A F M Yusuf (© 2009 Journal of Bangladesh Academy of Sciences, 2017)
This article was published in the Journal of Bangladesh Academy of Sciences [© 2009 Journal of Bangladesh Academy of Sciences] and the definite version is available at: http://dx.doi.org/10.3329/jbas.v33i1.2950